2021
DOI: 10.1177/2041669521989731
|View full text |Cite|
|
Sign up to set email alerts
|

Smells Influence Perceived Pleasantness but Not Memorization of a Visual Virtual Environment

Abstract: The present study aimed to investigate whether the perception of still scenes in a virtual environment in congruent versus incongruent condition can be influenced by odors. Ninety healthy participants were divided into three groups, including two experimental virtual reality (VR) environments: a rose garden, an orange basket, and a control condition. In each VR condition, participants were exposed to a rose odor, an orange odor, or no odor, resulting in congruent, incongruent, and control conditions. Participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…Recent evidence indicates that VR with multisensory stimuli may elicit a positive impact on users ( Melo et al, 2020 ). However, only a few studies employed multisensory VR to focus on the effects of virtual nature, and only the olfactory stimulus was considered, while other popular sensory stimuli such as haptics were not included ( Hedblom et al, 2019a ; Sabiniewicz et al, 2021 ). According to Hedblom et al (2019a) , the olfactory stimuli of nature may be better at decreasing stress than visual stimuli, which could be related to the odor of trees ( Ikei et al, 2015 ).…”
Section: Limitations Of Virtual Naturementioning
confidence: 99%
“…Recent evidence indicates that VR with multisensory stimuli may elicit a positive impact on users ( Melo et al, 2020 ). However, only a few studies employed multisensory VR to focus on the effects of virtual nature, and only the olfactory stimulus was considered, while other popular sensory stimuli such as haptics were not included ( Hedblom et al, 2019a ; Sabiniewicz et al, 2021 ). According to Hedblom et al (2019a) , the olfactory stimuli of nature may be better at decreasing stress than visual stimuli, which could be related to the odor of trees ( Ikei et al, 2015 ).…”
Section: Limitations Of Virtual Naturementioning
confidence: 99%
“…A study by Piqueras-Fiszman & Spence [59] has shown that people have strong crossmodal associations with products, and incongruency with these sensory expectations ''annoys'' the consumer [68]. Albeit, semantic congruency can increase its perceived pleasantness [57,61,64]. It is well known that adding additional sensory dimensions to virtual and augmented reality applications can increase the sense of presence (see [20] for a review).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence for the ability of odors to create particularly positive experiences in VR was recently shown in a study that demonstrated that odors increased the pleasantness of visual scenes in a virtual environment [73]; in another study, the presence of congruent odors augmented the desirability of and cravings for visual presentations of food in a virtual environment [74]. These examples illustrate the potency of odors to augment positive experiences in VR and their potential for therapeutic benefits.…”
Section: Reappraisal Of a Traumatic Memory With Ovrmentioning
confidence: 91%